The Tianjin Mental Health Survey (TJMHS): study rationale, design and methods. Issue 3 (21st October 2016) - Yin, Huifang; Phillips, Michael R.; Wardenaar, Klaas J.; Xu, Guangming; Ormel, Johan; Tian, Hongjun; Schoevers, Robert A.
Abstract: Mental health in China is of growing concern to both policy‐makers and researchers. The Tianjin Mental Health Survey (TJMHS) was conducted between July 2011 and March 2012 to assess the prevalence and risk factors of mental disorders in the context of recent economic growth and other socio‐demographic changes in Tianjin, a municipality of 13 million on China's eastern seaboard. A multistage cluster random sample selected using probability proportionate to size methods participated in a two‐phase screening procedure: 11, 748 subjects 18 or older were screened for risk of psychopathology and then an enriched risk‐proportional subsample of 4, 438 subjects was interviewed by psychiatrists using an expanded Chinese version of the Structured Clinical Interview for Diagnostic and Statistical Manual, Fourth Edition (DSM‐IV) Axis I disorders (SCID). The study also collected information about the impairment associated with mental disorders, mental health literacy, the stigmatization of mental disorders, and help‐seeking behavior for psychological problems. This paper provides a detailed overview of the study rationale, objectives, field procedures, and pattern of response. It highlights several of the methodological challenges of maintaining quality control of a complex epidemiological study in the Chinese setting, issues that are relevant to other community‐based epidemiological studies in low‐ and middle‐income countries.